Immunogenic oncolysis by tigilanol tiglate - Jonathan G. Pol; Manuela Lizarralde-Guerrero; Guido Kroemer (OncoImmunology)
Tigilanol tiglate is an oncolytic small molecule that is undergoing clinical trials. A recent study revealed the capacity of this pyroptosis inducer to elicit hallmarks of immunogenic cell death. In addition, intratumoral injection of tigilanol tiglate can sensitize subcutaneous cancers to subsequent immune checkpoint inhibitors targeting CTLA-4 alone or in combination with PD-1.